Imaging Mass Spectrometry for Characterization of Atrial Fibrillation Subtypes. Issue 6 (13th June 2018) - Klein, Oliver; Hanke, Thorsten; Nebrich, Grit; Yan, Junfeng; Schubert, Benedikt; Giavalisco, Patrick; Noack, Frank; Thiele, Herbert; Mohamed, Salah A.
Abstract : Purpose: Atrial fibrillation (AF) is a cardiac arrhythmia characterized by a rapid and irregular heart rhythm. AF types, paroxysmal (PX), persistent (PE), and long‐lasting persistent (LSP), require differences in clinical management. Unfortunately, a significant proportion of AF patients are clinically misclassified. Therefore, the aim of this study is to prove that MALDI‐Imaging (IMS) is valuable as a diagnostic aid in AF subtypes' assessment. Experimental design: Patients are clinically classified according to the guidelines of the European Society of Cardiology. FFPE tissue specimens from PE, PX, and LSP subtypes are analyzed by MALDI‐IMS and evaluated by multi‐statistical testing. Proteins are subsequently identified using LC‐MS/MS and findings are confirmed by immunohistochemistry and through the determination of potential fibrosis via histopathology. Result: Determined that characteristic peptide signatures and peptide values facilitate to distinguish between PE, PX, and LSP arterial fibrillation subtypes. In particular, peptide values from alpha 1 type I collagen (CO1A1) are identified that are significantly higher in LSP and PE tissues but not in PX myocardial AF tissue. These findings are confirmed by immunohistochemistry and through the determination of potential fibrosis via histopathology. Conclusion and relevance: These results represent an improvement in AF risk stratification by using MALDI‐IMS as a promising approach for AF tissue assessment.